2014
DOI: 10.1016/j.addr.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical forces in the skeleton and their relevance to bone metastasis: Biology and engineering considerations

Abstract: Bone metastasis represents the leading cause of breast cancer related-deaths. However, the effect of skeleton-associated biomechanical signals on the initiation, progression, and therapy response of breast cancer bone metastasis is largely unknown. This review seeks to highlight possible functional connections between skeletal mechanical signals and breast cancer bone metastasis and their contribution to clinical outcome. It provides an introduction to the physical and biological signals underlying bone functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 251 publications
1
29
0
Order By: Relevance
“…These results strongly suggest that mammalian cells can discriminate between different types of mechanical stimuli. Theoretical models have previously demonstrated that shear stresses induce more cell membrane deformation than stretchrelated stimuli (Lynch and Fischbach, 2014;McGarry et al, 2005). Direct comparison of mechanisms involved in hypotonic pressure- The relative contributions (determined from genetic and pharmacological interventions, see Table S6) of each ATP release route were added together.…”
Section: Dependence On Mechanical Stimulusmentioning
confidence: 99%
“…These results strongly suggest that mammalian cells can discriminate between different types of mechanical stimuli. Theoretical models have previously demonstrated that shear stresses induce more cell membrane deformation than stretchrelated stimuli (Lynch and Fischbach, 2014;McGarry et al, 2005). Direct comparison of mechanisms involved in hypotonic pressure- The relative contributions (determined from genetic and pharmacological interventions, see Table S6) of each ATP release route were added together.…”
Section: Dependence On Mechanical Stimulusmentioning
confidence: 99%
“…Exercise oncology (i.e. the application of exercise medicine in cancer) has also continued to broaden, with several novel avenues being explored through preclinical orthotopic models that have the potential to significantly improve outcomes in advanced prostate cancer patients once translated to human clinical trials [47,48,49 && ,50 && , [51][52][53][54]. Indeed, the impressive ability of exercise to potentially modulate cancer-specific outcomes is of direct clinical interest and warrants rigorous scientific inquiry.…”
Section: Exercise Medicinementioning
confidence: 99%
“…For example, aerobic exercise has been shown to stimulate natural killer cell production, mobilization and infiltration in to tumours, producing an approximate 60% reduction in tumour incidence and growth across several different preclinical tumour models [68 && ]. Similarly, controlled mechanical compressions of skeletal sites with known bone metastases have been shown to interfere with tumour-driven dysregulation of osteogenesis, producing an approximate 80% reduction in tumour growth rate in osteolytic models, while preserving skeletal integrity by approximately 70% in loaded versus unloaded conditions [47]. Cautiously, these preclinical findings use animal models over disparate time-periods, and require confirmatory human trials, some of which are currently in progress .…”
Section: Key Pointsmentioning
confidence: 99%
“…The substrate modulus (E s ) of the scaffolds is controlled by the M w of the polyester triol (compliant, 3000 g mol À 1 ; rigid, 300 g mol À 1 ) to attain values representative of collagen (5 MPa, compliant), trabecular bone (266 MPa, rigid) or cortical bone (871-11 500 MPa). 36,37 Cell viability, proliferation and metabolic activity. Trypan Blue cell viability, live/dead staining (calcein/propidium homodimer) or MTS assays (CellTiter 96 Aqueous Non-Radioactive Cell Proliferation Assay, Promega, Madison, WI, USA) can be performed as per the manufacturers' protocols.…”
Section: D Models Using Synthetic Materialsmentioning
confidence: 99%